Implementasi Peraturan Daerah Kabupaten Ponorogo Nomor 5 Tahun 2011 Tentang Ketertiban Uum dan Ketenteraman Masyarakat (Studi Penertiban Pedagang Kaki Lima di Kawasan Alun-Alun Ponorogo) - Susanti, Nopa Lilik; Handoko, Rudy; Sukarno, Sukarno (Universitas 17 Agustus 1945 Surabaya, 2019)
Regional Regulation No. 5 of 2011 on Public Order and Communal Peace is one of the rules of Local Government which is a public policy in which the implementation of public order is necessary to assert the policy. Judging from the state of public places many street vendors still sell around the sidewalks, roads, road intersections, especially in the area of Aloon Aloon Ponorogo.Â The intended aims of this study are first, to find out how the implementation of Local Regulation Number 5 Year 2011 about Public Order and Communal Peace (Study on the Order of Traditional Foot Trader in Aloon-Aloon Ponorogo Area).Â Second, to determine the factors that affect the implementation of the Local Regulation on the Traditional Foot Trader in order to maintain the discipline in the area of Aloon Aloon Ponorogo. The theory used in this research refers to Van Meter Theory and Van Horn. To support this study, the researcher used 8 people as informants by using qualitative data analysis as the data analysis in this study. Based on the result of this study, it can be concluded that theImplementation of Local Regulation Number 5 Year 2011 on Public Order and Communal Peace on the Ordering of Traditional Foot Trader in Aloon-Aloon Ponorogo Area until now has been running well in the disciplining but there is no arrangement of places for Traditional Foot Trader. Moreover, several factors that the regulation of the Local Regulation are due to the lack of infrastructure and human resources in disciplining traditional foot trader. This happens because there is no special fund prepared for the arrangement of street traders. Key words: Implementation, Regional Regulation, Traditional Trader